INSTAGRAM AS A SELF PRESENTATION MEDIA FOR YOUNG MOTHER IN MEDAN CITY - Nurbani; Ananda, Sabilla Tri (Komunika, 2024)
The presence of social media gives new habits in people's lives, Including the group of mother. The phenomenon that is prevalent nowadays is the habits of mothers who regularly uploaded on Instagram, Reviews their parenting activities and childrens's schedule. In this research, using the Self Presentation theory from Erving Goffman, aims to find the Strategy of Self Presentation is done by Instagram users and the implication of the use of social media to parenting at home. The research method is conducted qualitatively with the data collection techniques through interviews and observation of Instagram accounts of mothers who are informants. Research informants are a new mom who are the active Instagram users with a golden age of children (0-5 years).